Contribution Of Arm Muscle Training To Smashing Ability In Badminton At Negeri 17 Bengkulu Utara Junior High School - Pebrian Gultom; Dwingki Marta Putra; Ajis Sumantri (Universitas Dehasen Bengkulu, 2026)
This study aims to see the contribution of arm muscle training to the smash ability of badminton sports at SMP Negeri 17 Bengkulu Utara. This type of research is correlation research. The sample of the study was 20 people. The instruments used in this study were hand pull up tests and Badminton Smash Skills. Based on the results of the study above, there is a contribution of arm muscle training to the smash ability in badminton sports at SMP Negeri 17 Bengkulu Utara, that arm muscle strength to the smash ability in badminton sports at SMP Negeri 17 Bengkulu Utara is 94.77% which means that arm muscle strength contributes to the smash ability in badminton sports at SMP Negeri 17 Bengkulu Utara.